Alice Rio, Legal practice and the written world in the Early Middle Ages: Frankish Formulae, c. 500-1000. (Cambridge Studies in Medieval Life and Thought), Cambridge University Press, Cambridge, 2009; 299 pp. ISBN 978-0-521-51499-6 - Peretó Rivas, Rubén (2011)
Fil: Peretó Rivas, Rubén.